The effects, mechanisms and strategies of daytime napping on athletes: a narrative review - Yu, H.; Yang, C.; Xu, C.; Zhang, Y. (European Journal of Applied Physiology, 2025)
Athletes generally suffer from insufficient sleep duration, lower sleep efficiency, and a high overall prevalence of insomnia. Daytime napping has been demonstrated to supplement nighttime sleep in athletes; however, recent controversial findings warrant further consideration. This review synthesized existing studies on the effects of daytime naps on athletes, explored potential mechanisms of daytime napping, and analyzed instances of ineffective interventions or negative outcomes. Daytime napping functions as a restorative strategy to counteract sleep deprivation or the post-lunch dip, assisting athletes in recovering anaerobic capacity, agility, reaction time, and alertness, with potential mechanisms including the reduction of sleepiness through adherence to circadian rhythms, decreased subjective soreness and fatigue attributed to autonomic functioning, and improved respiratory performance. The optimal nap period occurs between 13:00 and 15:00, with a 5-6 h interval between morning awakening and nap initiation. Depending on the athlete`s nighttime sleep, opt for a 20 ~ 40 or 60 ~ 90 min nap with at least 60 min between the nap and subsequent exercise to reduce sleep inertia. The intervention efficacy of daytime napping was correlated with exercise intensity. A nap program must be developed based on the specific athletic demands of the sport in practical application.